2015
DOI: 10.21157/j.ked.hewan.v9i2.2808
|View full text |Cite
|
Sign up to set email alerts
|

PENINGKATAN TNF-α DAN INDEKS APOPTOSIS PADA TULANG MENCIT YANG DIINFEKSI Toxoplasma gondii

Abstract: Penelitian ini bertujuan mengetahui peningkatan tumor necrosis factor-alpha (TNF-α) dan indeks apoptosis pada tulang mencit yang  diinfeksi Toxoplasma gondii (T. gondii). Tiga puluh dua ekor mencit dibagi menjadi dua kelompok. Kelompok 1 (K1), merupakan kelompok kontrol, tidak diinfeksi sedangkan Kelompok 2 (K2) diinfeksi dengan 10 takizoit T. gondii secara intraperitoneal. Enam hari setelah infeksi mencit dikorbankan, diambil tulang femur dan dilakukan pembuatan preparat histologis dengan pengecatan immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In this study, it showed that congenitally T. gondii infection induced increased expression of TNF-α and IFN-γ in the skull of pups. This discovery completed our previous studies that also showed that T. gondii infection increased expression of TNF-α and IFN-γ (Suwanti, 2006;Suwanti, 2008;Suwanti and Mufasirin, 2015).…”
Section: A B a B Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In this study, it showed that congenitally T. gondii infection induced increased expression of TNF-α and IFN-γ in the skull of pups. This discovery completed our previous studies that also showed that T. gondii infection increased expression of TNF-α and IFN-γ (Suwanti, 2006;Suwanti, 2008;Suwanti and Mufasirin, 2015).…”
Section: A B a B Discussionsupporting
confidence: 61%
“…However reduced or increased apoptosis from normal may result in a particular pathology (Favaloro et al, 2012). Previous studies showed that acute toxoplasmosis induced apoptosis in liver and spleen (Mordue et al, 2001), trophoblast (Suwanti et al, 2006) or femur (Suwanti and Mufasirin 2015). On the other hand, accoding to Mordue et al (2001) and Nishikawa et al (2007), apoptosis in toxoplasmosis occurs in noninfected cells.…”
Section: A B a B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that T. gondii infection inhibits the apoptosis process in the retina [Tabel 1 and Figure 2]. The decreasing of apoptosis index in this research may be the explanation about the failed development of the newborn mice retina [ Figure 1c] and it is different with the result of the previous research that T. gondii infection caused increasing apoptosis in the skull and brain of newborn mice [8,9].…”
Section: Vmic 2017mentioning
confidence: 54%
“…In pregnant mice infected by T. gondii, increased trophoblast apoptosis was observed and was associated with increased FAS expression in trophoblast cells and IFN-γ and TNF-α in decidual cells [5]. T. gondii infection-induced apoptosis was also observed in femur bone marrow cells of mice and was associated with increased TNF-α expression [6]. TNF-α, a multifunctional cytokine, has been detected in many tissues including ovary, oviduct, uterus, and placenta and is expressed in embryonic tissues.…”
Section: Introductionmentioning
confidence: 99%